TAXONOMIA INTEGRATIVA EM LIQUENS PARMELIOIDES (PARMELIACEAE) DO BRASIL - Andressa Silva Rodrigues (2023)
Lichenized fungi comprise different organisms functioning as a self-sustaining ecosystem, a complex form of beneficial mutualistic life between fungi, green algae, and/or cyanobacteria, in addition to other microorganisms. They have more than 19 thousand known species, with Parmeliaceae the most diverse, and divided into two subfamilies: Protoparmelioideae and Parmelioideae. The latter is still informally subdivided into seven clades, with the Parmelioid clade having predominantly foliose representatives, accounting for around 67% of the family’s diversity. For many years, lichens have been identified based only on morphological characteristics, but with molecular advances, new tools for identifying these organisms gained space, such as the use of DNA barcoding, and more currently its association with integrative taxonomy. This approach aims to use different data sources for specific identification or delimitation and has presented the best results among the most current studies. Thus, our study aims to use an integrative approach and DNA barcoding (based on the nuITS marker) in species of the Parmelioid clade of Parmeliaceae from some localities in Brazil. In the first chapter, we combined two species Canoparmelia amazonica and Myelochroa lindmanii into Parmelinella. We confirmed the positioning of these species through molecular phylogeny (nuITS), thus proposing the combination of both under the genus Parmelinella. In addition, we also provide morphological and chemical descriptions and images, subsidizing the new classification. In the second article, we propose Hypotrachyna neohorrescens as a new species (subgenus Parmelinopsis). Hypotrachyna neohorrescens was closely related to H. mcmulliniana, but with low resolution using only the nuITS marker. The phylogenetic distinction of both was possible only with concatenated markers (nuITS+mtSSU). Morphologically, both species also present subtle differences. Moreover, we did not find morphological or chemical differences between Hypotrachyna neohorrescens and H. horrescens, but genetically, they present high divergences, thus being considered cryptic species. In the third and final chapter, we carried out the integrative identification of 90 specimens of lichens. Initially, we identified based on morphology, finding 39 morphospecies. Then molecular identification was carried out through DNA barcoding (nuITS marker), using BLASTn to verify the species closest to the study sequences and later we reconstructed the phylogenies by genus and used as homonymous sequences those available in the public database – GenBank. Based on the results of the three approaches (DNA barcoding, BLASTn analysis, and phylogeny), Among the 39 morphospecies, 22 contained homonymous sequences, i.e., sequences with the same name in the GenBank database. However, the phylogeny results show that 20 of these morphospecies grouped with sequences of the same identity, while 10 also presented distinct species in the same clade. Among the 17 morphospecies without homonymous sequences, only six were genetically distinct from the other sequences in GenBank, while the others showed some incongruity between the approaches. We found at least 22 cases of possible species complexes in our data, which were not resolved using only the nuITS marker. Our results corroborate recent studies that have already highlighted the lack of resolution of the nuITS marker in species complexes. Thus, making the task of using only DNA barcoding as a specific identification tool even more challenging.